Study on relationships of wind velocity, temperature and measurement precision of relative humidity - HUANG Xiao-yin; ZHOU Ping (浙江大学学报. 农业与生命科学版, 2007)
Psychrometric method is widely used to measure the air relative humidity in dryness processing of agricultural products. The experiments about the relationships of the wind velocity v, temperature t and relative humidity U were made in temperature-humidity controlling cabin. The results indicate that the dowm limit of v is 0.2 m·s-1 and has no influence on the measurement accuracy, regarding v as 2.5 m· s-1 when v>2.5 m·s-1. The results also show that psychrometer constant A is hardly effected by the temperature when t<40℃, and it is proportional to t2/3 within 40℃<t<70℃; The relationship of A and t becomes complication when t>80℃. A formula about A is proposed within 40℃<t<70℃, and it is demonstrated that the error of the relative humidity calculated by this formula is less than 1.5% R. H, when 0.2<v< 4 m·s-1，40℃<t<70℃ and 30% <U<90% R. H.